Mediação da informação em biblioteca escolar por meio da Cultura Maker: uma análise dos projetos desenvolvidos pela Biblioteca do CCBEU - RIBEIRO, Jean Libório (2017)
Investigates the mediation of information in school library through the Maker Culture, making an analysis of the projects developed by CCBEU Library. Specifically, it was sought to know how this methodology of american education, applied in the school library is an excellent mediator of the information between user and library, and of how this methodology would dynamize the process of use of the library.It uses bibliographic research, taking advantage of the information that is available in books, theses, dissertations and scientific articles to serve as a basis for discussions of the theoretical framework. It also uses field research, done together with the CCBEU librarian, so that it can analyze the manager profile as well as user analysis of the library. It raises primary data through a questionnaire with open and closed questions to analyze the satisfaction of the users with the activities of the library and to understand if they have a profile that matches what the Maker activities need.It presents the results of an interview recorded with the librarian in order to analyze her profile as a manager precisely due to her experience in library management as well as her familiarity with the Maker Culture. It concludes that school library management needs to be done by an active manager, who is linked to more modern methods of mediation in a way that optimizes and dynamizes the library recognition process more and more with it is supporting institution and then is valued by the society in general.